Empowering Dasawisma with the Spirit of Independence toward Welfare - Dila Erlianti; Irawati Irawati; Nurhaliza Nurhaliza; Tri Utami (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
This community service program was motivated by the suboptimal role of Dasawisma as a grassroots community organization in improving family welfare. Several Dasawisma groups still faced challenges in organizational management, low member participation, and limited understanding of productive and sustainable activity management. The objective of this program was to strengthen the organizational capacity of Dasawisma, increase member participation, and foster a spirit of solidarity and independence toward family welfare. The methods applied included a participatory approach through counseling sessions, group discussions, simple organizational management practices, and mentoring of Dasawisma activities. The results indicated an improvement in members’ understanding of organizational functions and the importance of structured activity planning. Members became more actively involved in preparing work programs, maintaining simple administrative records, and implementing productive and social activities. Behavioral changes were also observed, including increased collective responsibility, stronger cooperation among members, and the emergence of several local leaders. Furthermore, the program fostered a new awareness that Dasawisma is not merely a routine meeting forum, but a platform for empowering women and families toward sustainable welfare improvement.